On a fixed point theorem of Fisher and Sessa - Gerald Jungck (International Journal of Mathematics and Mathematical Sciences, 1990)
A fixed point theorem of Fisher and Sessa is generalized by replacing the requirements of commutativity and nonexpansiveness by compatibility and continuity respectively.